2008
DOI: 10.1007/s00534-007-1236-3
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder agenesis with a stone in the cystic duct bud

Abstract: An 84-year-old woman was admitted to the hospital because of pyloric stenosis caused by gastric cancer. Abdominal computed tomography and magnetic resonance imaging failed to demonstrate the gallbladder, but showed a gallstone in a duct-like structure parallel to the common bile duct. When laparotomy was performed, the gallbladder and the fossa were not observed, and a blind-end duct, similar to a cystic duct, was found beside the common bile duct. Incisional exploration of the common bile duct was done after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“… 6 In humans, most patients are asymptomatic, but some show clinical signs, including abdominal pain, nausea and jaundice that is sometimes associated with intra- and/or extrahepatic cholelithiasis. 1 , 12 17 Dogs with gallbladder agenesis have often been reported in the absence of clinical signs; half of canine cases are asymptomatic and a common clinical finding is increased liver enzyme activity. 2 5 In cats, one previous case report documented a cat with gallbladder agenesis diagnosed from ultrasonography and exploratory laparotomy showing clinical signs in association with inflammatory bowel disease, cholangiohepatitis and pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 In humans, most patients are asymptomatic, but some show clinical signs, including abdominal pain, nausea and jaundice that is sometimes associated with intra- and/or extrahepatic cholelithiasis. 1 , 12 17 Dogs with gallbladder agenesis have often been reported in the absence of clinical signs; half of canine cases are asymptomatic and a common clinical finding is increased liver enzyme activity. 2 5 In cats, one previous case report documented a cat with gallbladder agenesis diagnosed from ultrasonography and exploratory laparotomy showing clinical signs in association with inflammatory bowel disease, cholangiohepatitis and pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“… 18 20 Previous studies have reported that 25–50% of human gallbladder agenesis presented with clinical symptoms related to choledocholithiasis. 1 , 12 17 In cats, congenital anomalies of the biliary tract may be a risk factor for the formation of choleliths, and clinical case reports have described cholelithiasis with congenital duplex gallbladder. 21 , 22 Some congenital malformations with ductal plate malformation have been considered a risk factors for bacterial infection and cholelithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Gotohda et al [5] stated that if the gallbladder is not visualized by imaging techniques, laparoscopy should be performed before laparotomy. However, laparotomy can be avoided and the risk of any possible complications reduced by the laparoscopic surgeon's awareness of the problems posed by this anomaly and a careful review of currently available diagnostic tests [16].…”
Section: Discussionmentioning
confidence: 99%
“…Acute gallbladder distension (hydrops) is unusual in pediatric age [ 1 , 2 ]. It may be a consequence of obstruction of the cystic duct caused by gallstones, cholangitis, sclerosing cholangitis, cystic fibrosis [ 3 ], congenital or postoperative biliary malformations [ 4 ], or benign or malignant lesions [ 5 , 6 ]. Laparoscopic cholecystectomy is usually warranted [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%